Inhibition enhancer of zeste homologue 2 promotes senescence and apoptosis induced by doxorubicin in p53 mutant gastric cancer cells. (16th April 2014) - Bai, J.; Ma, M.; Cai, M.; Xu, F.; Chen, J.; Wang, G.; Shuai, X.; Tao, K.
Abstract Objectives Enhancer of zeste homologue 2 (EZH2) is crucially involved in epigenetic silencing by acting as a histone methyltransferase. Although EZH2 is overexpressed in many cancers and is involved in malignant cell proliferation and invasion, the role of EZH2 in senescence induced by DNA damage has up to now remained largely unknown. In this study, we sought to explore the outcome of EZH2 depletion along with exposure of doxorubicin (DOX), and related mechanisms, in gastric cancer cells. Materials and methods Here, senescence induced by DNA damage was achieved in gastric cancer cells by DOX treatment. EZH2 was downregulated by transfection with siRNA or treated with (‐)‐epigallocatechin‐3‐gallate, a targeted inhibitor. Senescence‐associated β galactosidase (SA‐β‐gal) and formation of senescence‐associated heterochromatin foci were used to identify cell senescence. To investigate effects of EZH2 depletion on the cell cycle, apoptosis and proliferation, flow cytometry and MTT analysis were employed. Changes in p53–p21 axis activation were detected by Western blotting. Results We found that cell proliferative arrest caused by DOX could be promoted by EZH2 depletion. Mechanistically, EZH2 depletion not only worked in coordination with DNA damage during the progression of cell senescence but also promoted apoptosis in p53 mutant cells. However, it had no cooperative relationship with DOX in p53 wild‐type cells. Conclusions These data help unravel a crucial role for EZH2 in senescence and apoptosis in gastric cancer cells and that p53 genomic status was associated with different cell responses to EZH2 silencing.